Development and validation of a HPLC method for the determination of metronidazole, oxytetracycline and furazolidone in veterinary formulations - Violeta Tauber (Giugiu); Viorica Chiurciu (Medicamentul Veterinar, 2014)
An isocratic reversed phase high performance liquid chromatographic method with DAD detection was developed for the analysis of metronidazole, oxytetracycline and furazolidone. The mobile phase consisted of pH 2.5 phosphate buffer solution, methanol and acetonitrile (70:18:12). The UV detection was carried out at 264 nm, and the flow rate was 1.100 mL/min. The separation was carried out on a Nucleosil C18 column, 5 µm 250 mmx4.6 mm, which was maintained at 25 0C. This method was validated by system suitability parameters, linearity, limits of detection and quantification, precision and accuracy